Chlamydia trachomatis as a probable cofactor in human papillomavirus infection in aboriginal women from northeastern Argentina - Deluca, Gerardo (2011)
Fil: Deluca, Gerardo. Universidad Nacional del Nordeste. Facultad de Medicina; Corrientes, Argentina.